Research on Cloud-Side Collaborative Meteorological Information Processing and Intelligent Services - Hongping SHU; Wang TANG; Fei LUO; Zhuoning ZHAO; Yaqiang WANG (天地一体化信息网络)
China has set up the largest and most comprehensive ＆quot;land-air-space＆quot; integrated automatic meteorological observation network and integrated meteorological observation system in the world.Meteorological informatization has put forward new demands for digital transformation.From the perspective of cloud edges synergy distributed technology, according to the technical characteristics of cloud, edge and side collaborative distributed technique of meteorological information processing, according to the real business situation of the China meteorological administration, the implementation possibility of the cloud, edge and side collaborative technique in meteorological information processing and service were analyzed, and a model driven cloud, edge and side collaborative system architecture and service architecture for the meteorological information processing was proposed.